NARRATIVAS SOBRE A PRAGA DE GAFANHOTOS NAS LOCALIDADES DE FAXINAL DO RIO DO COURO, FAXINAL DOS MELLOS E RIO DO COURO: IRATI-PR, DÉCADA DE 1940 - Maneira, Regiane (2013)
The "faxinal" is considered a cultural practice found in central - southern state of Paraná , in which the land is divided into land and land planted to create. Although it was a common practice in this region , demonstrations , practices , beliefs and symbols of that culture , are still poorly studied and / or known . This worked were designed to identify the cultural practices of those residents in the years before the infestation of locusts that occurred in the late 1940s , specifically in 1946 , as well as the meanings attributed to the arrival of these insects in the localities of Faxinal do Rio do Couro, Rio do Couro e Faxinal dos Mellos, which are located in rural areas in the municipality of Irati - PR . Still , we make some notes on how certain cultural practices were " reconfigured " by the locals after the destruction of crops by locusts . The methodology used in the analysis consisted of interviews , which were made with residents of the Faxinal do Rio do Couro, Rio do Couro e Faxinal dos Mellos witnessed the infestation of locusts . Other sources were also used letters , egovernment, newspaper reports , telegrams and photographs that reference this event . As a theoretical framework used some concepts of Michel de Certeau , such as " practical " and " convenience " in order to understand how the daily life of these residents was reinvented during the occurrence of locusts and the relationship of convenience that settled .